Isolation and identification of bioactive compounds from seaweed Sargassum ilicifolium - Afnani Alwi @Ali (Terengganu: Universiti Malaysia Terengganu, 2013)
Three species or Sargassum sp. (S. ilicifolium, S. pofycystum and S. oligocystum) have been screened for antioxidant (DPPH method), cytotoxicity (MTT Assay), antimicrobial (Disc Diffus ion Method) and anti-amoebic bioactivities. All methanol crude extracts showed DPPH free radical scavenging, cytotoxic to several cell lines which include HL-60 (leukemic) and MCF-7 (breast cancer), anti-bacterial and anti-amoebic activity. However methanol ex tract of S. oligocystwn is inactive against all microbes tested. Only S.ilicifolium elected to be investigate further, based on their promising bioactivity results and the availability of the sample.